Coordination between school and university for the experimental work of determination of level of antioxidants in food samples and drinks using Briggs-Rauscher reaction and TRL/luminescence fingerprinting - Habib, Nusrat (fi=Turun yliopisto|en=University of Turku|, 2018)
The actual theme of this thesis is to develop co-operation between schools and university and hence to provide the students an opportunity to utilize the university laboratory equipment in the experimental work. This research work is based on developmental techniques in which the experimental work was first tried with the first group of secondary school students in Opi-LUMA laboratory of the chemistry department of University of Turku and was later modified for upper secondary school students according to their level. Literature review helped to discover/select the experimental methods to be used in this context. The data collected through questionnaires during the experiments was later analysed to see the learning outcomes and interest of the students visiting Opi-LUMA laboratory. The international and Finnish curriculum books were thoroughly analysed using content analysis technique to investigate if the topic was explained well highlighting the importance of antioxidants in daily diet. The main objective of this research is to develop the laboratory work for “determination of level of antioxidants in food and drinks”. It started with the literature review to investigate the work done previously in this context and then check the objectives of the chemistry curriculum outlined by Finnish National Board of Education. Experimental work was developed based on the observations and the feedback obtained from the first trial with the first group of visiting students. Feedback was reported in the form of questionnaires filled by the students expressing their interest in the topic and hoping for more coordination between the university and the school. The school teacher of the visiting students also considered such co-ordination important and beneficial for the students as students got an opportunity to utilize the Opi-LUMA laboratory equipment which is usually not available in school laboratories. Students learnt about the importance of taking antioxidants regularly in daily diet. Briggs-Rauscher reaction was more interesting for all students due to series of colour changes involved which could very easily help them to know the relative concentration of antioxidants in the food samples. Luminescence fingerprinting used for testing adulteration in food was totally new technique introduced to upper secondary school students. These techniques proved to be very fruitful to make chemistry relevant to life. Content analysis of the books revealed that the topic of antioxidants has not been described well in Finnish curriculum as in the international curriculum books. This research work finds the coordination between schools and university to be a powerful mean to develop students´ interest in chemistry by making chemistry more relevant to life, hence motivating them to take more chemistry subjects in universities.